2022
DOI: 10.3389/fpubh.2022.813378
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a MEURI Program for the Use of High Dose Ivermectin in COVID-19 Patients

Abstract: BackgroundIn the absence of antiviral alternatives, interventions under research for COVID-19 might be offered following guidelines from WHO for monitored emergency use of unregistered and experimental interventions (MEURI). Ivermectin is among several drugs explored for its role against SARS-CoV-2, with a well-known safety profile but conflicting data regarding clinical utility for COVID-19. The aim of this report is to inform on the results of a MEURI Program of high-dose ivermectin in COVID-19 carried out b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions. The effectiveness could be particularly strong at high doses ( Krolewiecki et al, 2021 ; Buonfrate et al, 2022 ; Mayer et al, 2022 ) and for severe SARS-CoV-2 infection ( Beltran Gonzalez et al, 2022 ; Hazan et al, 2022a ; Zubair et al, 2022 ), and one must consider that the effective dose is very affected by food co-administration ( Food and Drug Administration, 2022 ). Thus, there is a tremendous need to ascertain, not whether but how IVM is ideally applied for SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Krolewiecki, et al, 2020;Elgazzar, et al, 2020). As well as mentioned by Mayer, et al, 2022, "MEURI interventions are applied when there are no treatments of proven efficacy, it is not possible to start clinical trials immediately, existing preliminary data support the intervention, the relevant regulatory, ethical and scientific authorities approve such use, resources are available to minimize risks and Informed consent is obtained from the patient". In Argentina's health system, the emergency of COVID-19 requires the urgent development of strategies to avoid the impact of the disease on our population, prevent the saturation of the health system and allow us to carry out adequate treatments to reduce the mortality of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this situation, the Ministry of Health of the Province considered a MEURI Program as a resource to attempt the monitored and controlled use of a treatment not approved for this indication but with preliminary results of adequate safety and potential efficacy. A recent work carried out by the Ministry of Health of La Pampa, Argentina (Mayer, et al, 2022) on a MEURI Program of high-dose Ivermectin in COVID-19 patients highlights the safety and possible efficacy of this drug for the management of COVID-19 patients.…”
mentioning
confidence: 99%